Kompetenzerweiterung durch studentische Kollaborationen in internationalen Begegnungsprojekten am Beispiel einer deutsch-niederländisch-polnischen Austauschseminarreihe - Adamczak-Krysztofowicz, Sylwia; Ciepielewska-Kaczmarek, Luiza; Jaszczyk-Grzyb, Magdalena (Glottodidactica, 2025)
A period spent abroad can be seen as a career-defining phase. Ideally, this development is experienced as a continuous learning process. As part of German Studies Institute Partnership (GIP) between Adam Mickiewicz University in Poznań (AMU), Radboud University in Nijmegen (RU) and Philipps University in Marburg (UMR), which builds on long-standing cooperation across the three countries in research on the teaching of German as a foreign language, students from Poznań, Marburg and Nijmegen are offered a trilateral project seminar once a year with a subsequent study trip. During such exchange seminars the participating students meet their fellow students on site at the three locations and collaborate in small project groups. On the basis of a quantitative-qualitative online survey of two initial German-Dutch-Polish exchange seminars, we aim to identify the potential of such formats for expanding selected areas of competence in prospective teachers. Building on the results, we intend to make initial suggestions regarding the competence profile of a (pluri-) culturally competent teacher.